Corporificar#5: uma proposta des(e)ducatica em dança - Nicole Blach Duarte de Carvalho (2024)
The research arises from the desire to deepen the studies developed in the master's degree in terms of basing an artistic-pedagogical approach, which has the act of dancing as its axis, and to elaborate a proposal for teaching in dance. It explores the act of dancing as an event seeking to highlight its interconnection with personal experiences and poetics and investigates teaching and learning processes in dance from practices of creation and composition with reference to the artistic work Embodying#. Qualitative and exploratory, the research is based on the autoethonographic approach, considering the researcher's professional experiences in the artistic and pedagogical field of dance over twenty years of work in the area, and its methodology is practice as research. It proposes a “deeducational” perspective on dance considering the act of dancing as a process of deconstruction, invention and destabilization of patterns. In this sense, it is aligned with contemporary dance thinking and has as main references assumptions of modern and postmodern dance located around the Judson Dance Collective. Its main theoretical contributions are Anna Halprin (1995), Banes (1994; 1999; 2003), Gil (1997; 2001), Dewey (2010), Laban (1978; 1990), Mary Wigman (1966) and expands dialogues in view of the works of Keleman (1992; 1994; 2017). It aims to improve a practical, artistic approach, focused on the expressive potential of movement and to present a proposal for teaching in dance that, by including self-awareness and self-perception as elements that constitute the microuniverse that shapes the dancing act, can expand knowledge of dance in the scene and beyond, increasing reflections about creative process, teaching and learning processes in the area.